STUDY ON ENERGY EXCHANGE PROCESSES IN NORMAL OPERATION OF METRO ROLLING STOCK WITH REGENERATIVE BRAKING SYSTEMS - Sulym, A. O.; Muzhychuk, S. O.; Khozya, P. O.; Melnyk, O. O.; Fedorov, V. V. (Science and Transport Progress, 2017)
Purpose. The analysis of the existing studies showed that the increasing of energy efficiency of metro rolling stock becomes especially important and requires timely solutions. It is known that the implementation of regenerative braking systems on rolling stock will allow significantly solving this problem. It was proved that one of the key issues regarding the introduction of the above-mentioned systems is research on efficient use of electric energy of regenerative braking. The purpose of the work is to evaluate the amount of excessive electric power of regenerative braking under normal operation conditions of the rolling stock with regenerative braking systems for the analysis of the energy saving reserves. Methodology. Quantifiable values of electrical energy consumed for traction, returned to the contact line and dissipated in braking resistors (excessive energy) are determined using results of experimental studies of energy exchange processes under normal operating conditions of metro rolling stock with regenerative systems. Statistical methods of data processing were applied as well. Findings. Results of the studies analysis of metro rolling stock operation under specified conditions in Sviatoshinsko-Brovarskaia line of KP «Kyiv Metro system» stipulate the following: 1) introduction of regenerative braking systems into the rolling stock allows to return about 17.9-23.2% of electrical energy consumed for traction to the contact line; 2) there are reserves for improving of energy efficiency of rolling stock with regenerative systems at the level of 20.2–29.9 % of electrical energy consumed for traction. Originality. For the first time, it is proved that the most significant factor that influences the quantifiable values of the electrical energy regeneration is a track profile. It is suggested to use coefficients which indicate the amount and reserves of unused (excessive) electrical energy for quantitative evaluation. Studies on determination of the quantifiable values of electricity recovery for analysis of energy saving reserve showed prospects for further development. Practical value. The obtained qualified values of excessive electric energy of regenerative braking can be applicable to construction of new or upgrading of the existing metro rolling stock provided that energy efficient technical solution for the utilization, preservation and storage of such electrical energy is developed.